(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Reconstruction of soft tissue defects involving the thumb, especially with exposed tendons or bones, remains a significant challenge in hand surgery. The first dorsal metacarpal artery flap has emerged as a reliable option, particularly when modified to include the sensory branch of the radial nerve. Objective: To present a clinical case utilizing a modified first dorsal metacarpal artery flap with inclusion of the sensory branch for coverage of a dorsal thumb soft tissue defect, and to review its advantages and outcomes in light of current literature. Methods: A female patient sustained a work-related injury resulting in a dorsal soft tissue defect of the left thumb with exposed extensor tendon at the proximal interphalangeal joint. Following initial wound stabilization, coverage was performed using a modified first dorsal metacarpal artery flap incorporating the superficial sensory branch of the radial nerve. Postoperative care included close monitoring, intramuscular Papaverine, and intravenous Unasyl. Results: The flap survived completely without necrosis or infection. The surgical site healed well, and the patient regained functional grip and returned to work within six months. Conclusion: The modified first dorsal metacarpal artery flap with integrated sensory nerve branch offers a reliable and functionally favorable solution for dorsal thumb soft tissue defects with tendon exposure. This technique provides durable coverage, sensory restoration, and aesthetic outcomes, and should be considered a first-line option in modern reconstructive hand surgery.